Stress-related psychiatric disorders - Al Bazzal, Abbas; Mtairek, Mohammad Ali; Awde, Mohammad Hadi; Kanso, Haidar; Hajj, Fatima; Al Amin, Fatima; Kazan, Zeinab; Mohammed, Nadia A.; Hamdar, Hiba (Progress in brain research, 2025)
Stress is a natural human emotion that motivates us to face difficulties and risks. Everyone experiences stress to some extent, but when it becomes chronic or reaches a level that cannot be managed, its effects begin to manifest. It is a common condition that most individuals confront, and its effects on the body and brain have become more obvious in recent years. Social and environmental interactions activate systemic reactions primarily controlled by the brain via immunological, neuroendocrine, and metabolic pathways. Long-term stress disrupts homeostasis, activating stress mediators that attempt to restore balance but frequently cause cumulative damage, particularly to the hippocampus, amygdala, and hypothalamus. Furthermore, persistent stress can have a direct and indirect effect on initiating psychiatric illnesses such as depression, anxiety, ADHD, and schizophrenia. Studies on neuroimaging show anatomical and functional alterations in stress-affected regions such as the prefrontal cortex and the hippocampus, which are linked to emotional dysregulation and cognitive decline. To better understand how stress affects psychiatric disorders and exacerbates their symptoms, this chapter will first discuss the molecular mechanism and neurobiological changes it can cause. It will then demonstrate various neuroimaging techniques for studying the effects of stress and offer potential treatments to mitigate these negative effects.